2020
DOI: 10.3390/su12208505
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Sustainability in the European Countries: A Panel ARDL Approach and a Dynamic Panel Threshold Model

Abstract: We analyze the fiscal sustainability hypothesis for a panel of 20 European Union countries from 2000 to 2019. In particular, we employ new econometric methodologies that, to the best of our knowledge, are applied for the first time to the study of sovereign fiscal policy sustainability in these economies. Specifically, we estimate the panel ARDL technique, distinguishing between short- and long-run coefficients because the order of integration of our variables is not the same. Moreover, a panel threshold model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
(84 reference statements)
1
4
0
2
Order By: Relevance
“…Therefore, for the selected SSA economies' real gross domestic product to improve, remittances must account for at least a 26.6 percent share of the yearly impact inflow to overcome the persistent human capital flight challenges in the region. This is comparable to the findings of a previous study [69]. As a result, a return to convergence will take four years on average, although authorities (i.e., government institutions and departments of the selected SSA countries, government agencies, and private organizations) may implement active policies and programs that can offer opportunities for decent work, wages, and favorable labor market participation for all who wish to seek employment, as well as providing traceable channels for remittance inflows into their countries to ensure the remittance system is easy to access as well as policies that will prevent human capital flight and brain drain.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, for the selected SSA economies' real gross domestic product to improve, remittances must account for at least a 26.6 percent share of the yearly impact inflow to overcome the persistent human capital flight challenges in the region. This is comparable to the findings of a previous study [69]. As a result, a return to convergence will take four years on average, although authorities (i.e., government institutions and departments of the selected SSA countries, government agencies, and private organizations) may implement active policies and programs that can offer opportunities for decent work, wages, and favorable labor market participation for all who wish to seek employment, as well as providing traceable channels for remittance inflows into their countries to ensure the remittance system is easy to access as well as policies that will prevent human capital flight and brain drain.…”
Section: Resultssupporting
confidence: 92%
“…By utilizing semiparametric formulations and exploring the explicit role of singularity in conditional covariance matrices, these studies reveal empirical insights into fiscal sustainability, examining fiscal adjustments, public debt dynamics, and the impact of joining economic unions like the EMU (European Monetary Union) on fiscal sustainability. Furthermore, (iii) panel analysis (Abeysinghe et al 2022;Bui 2019;Feld et al 2020;Polat and Polat 2021;Ramos-Herrera and Prats 2020). These studies, employing various panel analysis techniques, contribute to understanding fiscal sustainability across different economies, identifying both sustainable and unsustainable fiscal trends, and providing insights into governments' reactions to increasing debt levels.…”
Section: Abstract Analysismentioning
confidence: 99%
“…Furthermore, (iii) panel analysis (Abeysinghe et al 2022;Bui 2019;Feld et al 2020;Polat and Polat 2021;Ramos-Herrera and Prats 2020). These studies, employing various panel analysis techniques, contribute to understanding fiscal sustainability across different economies, identifying both sustainable and unsustainable fiscal trends, and providing insights into governments' reactions to increasing debt levels.…”
Section: Abstract Analysismentioning
confidence: 99%
“…From an empirical point of view, Forni et al [20] simulated a DSGE model of a currency union to assess the macro-economic implications of permanently reducing the public debtto-gross domestic product (GDP) ratio in European area countries, and Ramos-Herrera and Prats [21] estimated both a panel autoregressive distributed lag model and a panel threshold model to analyze long-term fiscal sustainability for a panel of 20 European countries. Fatás and Summers [22] observed that the global financial crisis permanently lowered the path of GDP while raising government debt levels, and they empirically explored the connections between these two findings.…”
Section: Literature Reviewmentioning
confidence: 99%